Pre-operative fasting guidelines: An update - Yasmin, Rubina; Khan, Sayed Akhter; Sarker, Paresh Chandra; Khan, Zakir Hossain (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
DOI: http://dx.doi.org/10.3329/jbsa.v22i1.18099 Journal of BSA, 2009; 22(1): 32-34